Penerapan Business Check Up Untuk Pemetaan Umkm - Bahrul Ulum Ilham (Syntax Idea, 2022)
The problem in this research is how to map MSMEs assisted by the Center of Integrated Services (CIS) SMESCo South Sulawesi using a business check-up. The use of business check-ups to determine the health condition of the business, and identify problems and sources of problems in the business. This research is a quantitative descriptive study using radar analysis. Radar charting is a graphical method for displaying multivariable data in the form of a two-dimensional chart of three or more quantitative variables represented on an axis starting from the same point. A total of 50 MSMEs filled out a business check-up which refers to the development of 8 MSME business aspects which include aspects of independence, aspects of innovation, aspects of courage to take risks, aspects of proactively capturing opportunities and markets, marketing aspects, and operational aspects., financial aspects, and HR aspects. The conclusion from the application of radar analysis in mapping MSMEs assisted by the SMESCo Center of Integrated Services (CIS) South Sulawesi shows that 8 aspects of MSME business check-ups are in a good category (radar 3-4), unless the financial aspect is in the sufficient category (radar 2-3). The highest aspect is the innovation aspect with a value of 3.67 and the lowest is the financial aspect with a value of 2.74. Based on these results, it is recommended to improve the performance of MSMEs assisted by the Center of Integrated Services (CIS) SMESCo South Sulawesi in the financial aspect.